كه‌رتبوون له‌ نێو پارته‌ سیاسییه‌‌كان له‌ باشوورى كوردستان 1975-1980 (‌یه‌کێتی نیشتمانیى كوردستان به‌‌ نموونه‌‌) - مسته‌فا, ئارام عه‌لى; جالل, كاوه طیب (Sulaimani Journal for Humanities, 2018)
Looking back to the history of Kurdish political parties, we see a lot of division, conflict and in- fighting among them compared to other global party split or defection in the political world arena except for (1975-1980), which was seen as a new phase in the political history of Southern Kurdistan. That phase was seen as a political pluralism in that part of Kurdistan, though it was گۆڤاری زانکۆی سلێمانی/ بەشی )B )زانستە مرۆڤایەتییەکان ژمارە )85( تشرینی یەکەمی 8105 59 something novel in the Kurdistan political spectrum. This opened a door for a lot of domestic problems, despite their struggle due to that a lot of political problems came about among the political parties, which split the parties. This had resulted domestic conflict among themselves, which they paid the price, because of that conflict they failed to get use from the Iran-Iraq war, which was a golden opportunity to unify themselves and moving forward their cause a step in the right direction.